1998
DOI: 10.1046/j.1523-1755.1998.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed graft function of more than six days strongly decreases long-term survival of transplanted kidneys

Abstract: Our results suggest a threshold effect in the lesions that ultimately results in long-term functional deficiency. In addition, we show that the need for dialysis is not an adequate criterium for DGF in terms of long-term outcome prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
140
2
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(157 citation statements)
references
References 25 publications
10
140
2
5
Order By: Relevance
“…41 Taken as a whole, these data suggest that recording KwRw may help to improve late clinical outcome and may be relevant in the context of poor long-term graft survival 42,43 when the early benefit of preventing acute rejection is censored.…”
Section: Discussionmentioning
confidence: 91%
“…41 Taken as a whole, these data suggest that recording KwRw may help to improve late clinical outcome and may be relevant in the context of poor long-term graft survival 42,43 when the early benefit of preventing acute rejection is censored.…”
Section: Discussionmentioning
confidence: 91%
“…Recipient sensitization, although variously defined, is a well-known risk factor for the occurrence of DGF (5,7,9,(29)(30)(31)(32). Furthermore, two studies have correlated high PRA and history of previous transplant with prolonged DGF (33,34). A possible mechanism accounting for these associations is humoral rejection or the development of an antibody response against the graft.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous study directly addresses risk factors for DGF duration, although some limited data are provided by a few studies that examine the impact of DGF duration on long-term graft outcomes (33,34,(39)(40)(41)(42). The factors identified by these studies as correlating with the duration of DGF were those classically associated with the risk of DGF, such as donor age, asystolic arrest, hemodynamic instability, cause of death, cold and warm ischemia times, and recipient history of previous transplant or PRA > 30% (33,34,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had conflicting results on the importance of DGF in the absence of acute rejection (AR), with some groups finding no effect (2) and other groups finding a DGF effect independent from early AR (3,4). In addition, GiralClasse et al (5) reported that DGF strongly decreases long-term survival of first cadaveric transplanted kidneys but only when lasting more than 6 d. The incidence of this complication has recently increased, possibly because of a larger use of marginal donor organs, which display a low renal reserve and a greater susceptibility to ischemia-reperfusion injury (4), and the adoption of higher concentrations of calcineurin inhibitors (CNI) to avoid early allograft rejection (6).…”
mentioning
confidence: 99%